A flow sheet for the conversion of lunar regolith using fluorine gas. Issue 7 (1st April 2020) - Turan, Evren M.; Stein, Samuel A.; Maharaj, Riddhi; Möller, Klaus P.
Abstract: This work reviews and expands upon the previous fluorination processes for in situ production of oxygen and silicon from lunar regolith. The process units were simulated and a flow sheet was developed to determine the product distribution and energy requirements. Our results show that 0.21 kg silicon and 0.32 kg oxygen can be produced per kg regolith processed with a total cooling duty of 17 MJ/kg regolith and electrical duty of 29 MJ/kg regolith. The payload mass required for the process is estimated as 16 kg/kg regolith processed per day.